Effects of Sinusoidal Vibrations on the Motion Response of Honeybees - Stefanec, Martin; Oberreiter, Hannes; Becher, Matthias A.; Haase, Gundolf; Schmickl, Thomas (Frontiers in Physics, 2021)
Vibratory signals play a major role in the organization of honeybee colonies. Due to the seemingly chaotic nature of the mechano-acoustic landscape within the hive, it is difficult to understand the exact meaning of specific substrate-borne signals. Artificially generated vibrational substrate stimuli not only allow precise frequency and amplitude control for studying the effects of specific stimuli, but could also provide an interface for human-animal interaction for bee-keeping-relevant colony interventions. We present a simple method for analysing motion activity of honeybees and show that specifically generated vibrational signals can be used to alter honeybee behaviour. Certain frequency-amplitude combinations can induce a significant decrease and other signals might trigger an increase in honeybees' motion activity. Our results demonstrate how different subtle local modulatory signals on the comb can influence individual bees in the local vicinity of the emitter. Our findings could fundamentally impact our general understanding of a major communication pathway in honeybee colonies. This pathway is based on mechanic signal emission and mechanic proprio-reception of honeybees in the bee colony. It is a candidate to be a technologically accessible gateway into the self-regulated system of the colony and thus may offer a novel information transmission interface between humans and honeybees for the next generation of 'smart beehives' in future beekeeping.